2019
DOI: 10.1111/1753-0407.12903
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil‐lymphocyte ratio as a predictor of kidney function decline among individuals with diabetes and prediabetes: A 3‐year follow‐up study

Abstract: Highlights This study is the first study to confirm that the neutrophil–lymphocyte ratio (NLR) is an independent predictive factor for kidney function decline among individuals with diabetes and prediabetes. Calculating the NLR is easy and inexpensive, so we believe that with more research support the NLR will be used as an effective indicator in the clinical management of individuals with diabetes and prediabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…A cross-sectional study observed a positive association between a higher NLR and the occurrence of both nephropathy and retinopathy in an Indian population ( 12 ). Additionally, an elevated NLR was correlated with diabetic nephropathy in other studies ( 10 , 28 ) and even served as an independent predictor of kidney function decline in individuals with DM ( 29 ). DR and nephropathy share common underlying mechanisms and often co-occur ( 30 ).…”
Section: Discussionmentioning
confidence: 62%
“…A cross-sectional study observed a positive association between a higher NLR and the occurrence of both nephropathy and retinopathy in an Indian population ( 12 ). Additionally, an elevated NLR was correlated with diabetic nephropathy in other studies ( 10 , 28 ) and even served as an independent predictor of kidney function decline in individuals with DM ( 29 ). DR and nephropathy share common underlying mechanisms and often co-occur ( 30 ).…”
Section: Discussionmentioning
confidence: 62%
“…AKI results from a complex interaction between hemodynamic, toxic and inflammatory factors[ 32 ]. Long-term follow-up showed that NLR was an independent predictor of kidney function decline among individuals with diabetes and prediabetes[ 33 , 34 ]. The elevation of NLR immediately after cardiac surgery and on postoperative day 1 was associated with an increased risk of postoperative AKI and 1-year mortality; NLR could assist with the risk stratification of AKI and mortality in high-risk surgical patients[ 7 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…En este sentido, se han propuesto varios marcadores biológicos que podrían indicar la gravedad de estos procesos inflamatorios. En los últimos años, el INL se ha sugerido como un indicador de inflamación subclínica y demostró ser un buen factor pronóstico para el desarrollo de complicaciones vasculares asociadas a la DM [11][12][13] . En este estudio, se evaluó el INL en una población ecuatoriana con DM2 y se encontró un incremento significativo en este marcador con respecto a los controles.…”
Section: Discussionunclassified